FLORAE MALESIANAE PRAECURSORES XII*SOME NOTES ON THE GENUS DICHAPETALUM (DICHAPETA- LACEAE) IN ASIA, AUSTRALIA, AND MELANESIA - P. W. LEENHOUTS (BRIN Publishing (Penerbit BRIN), 1956)
Some general notes are given on the morphology of the inflorescence and flowers in the genus Dichapetalum and on the nomenclature of the generic name Dichapetalum. An attempt has been made to revise the c. 40 species described in it from the Indo-Australian area. It appeared necessary to reduce a large number of specific names to synonymy. In the present paper 16 species have been recognized among which 4 are new. Besides, a number of infraspecific taxa have been distinguished. Pentastira Ridley, referred to the Icacinaeeae, has been reduced to Dichapetalum. A census is given of Indo-Australian species including one extra-Malaysian one, 16 D. vitiense.